Deoxynivalenol in food and feed: Recent advances in decontamination strategies - Li, Yingfeng; Gao, Huihui; Wang, Ru; Xu, Qing (Frontiers in Microbiology, 2023)
Deoxynivalenol (DON) is a mycotoxin that contaminates animal feed and crops around the world. DON not only causes significant economic losses, but can also lead diarrhea, vomiting, and gastroenteritis in humans and farm animals. Thus, there is an urgent need to find efficient approaches for DON decontamination in feed and food. However, physical and chemical treatment of DON may affect the nutrients, safety, and palatability of food. By contrast, biological detoxification methods based on microbial strains or enzymes have the advantages of high specificity, efficiency, and no secondary pollution. In this review, we comprehensively summarize the recently developed strategies for DON detoxification and classify their mechanisms. In addition, we identify remaining challenges in DON biodegradation and suggest research directions to address them. In the future, an in-depth understanding of the specific mechanisms through which DON is detoxified will provide an efficient, safe, and economical means for the removal of toxins from food and feed.